2015
DOI: 10.4103/2229-5151.158404
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of the burden of trauma in Makurdi, Nigeria

Abstract: Background:Trauma leads to considerable morbidity and mortality. The aim of this study is to elucidate the pattern and characteristics of trauma at Benue State University Teaching Hospital (BSUTH), Makurdi, Nigeria.Materials and Methods:Case records of all patients who presented to the Accident and Emergency (A and E) Department with trauma between January and December 2013 were analyzed for demographic data, types of injuries sustained, causes and circumstances of injuries, as well as outcome of treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 7 publications
5
17
0
Order By: Relevance
“…The patients in this study were predominantly male 65.3% (n = 94). This finding is similar to previously done studies such as those by Botchey et al in Kenya in 2017 [12] , Elachi et al in Nigeria in 2015 [13] , and Chokotho et al in Malawi in 2014 [14] . Differences in playtime behaviour between genders may be one reason for such findings, as well as higher activity levels, greater freedom to play alone, and increased involvement in risky sports among males.…”
Section: Discussionsupporting
confidence: 93%
“…The patients in this study were predominantly male 65.3% (n = 94). This finding is similar to previously done studies such as those by Botchey et al in Kenya in 2017 [12] , Elachi et al in Nigeria in 2015 [13] , and Chokotho et al in Malawi in 2014 [14] . Differences in playtime behaviour between genders may be one reason for such findings, as well as higher activity levels, greater freedom to play alone, and increased involvement in risky sports among males.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with many previously published studies, our study also shows male predilection for injuries, males 67.9 %( n=595) and females 32.1 %( n=276). 21,22,23 The present study revealed that 3-5 years age group is the most common victim of trauma,39%(n=340). 6-10.9 years 20.7%(n=2038) has been reported as the most frequently injured age group 10 A study conducted in India reported that 11-15 years comprised the most common age group involved in trauma.…”
Section: Discussionsupporting
confidence: 49%
“…This is similar to a report in Kenya where males constituted 73.5% of all trauma admissions and 57.6% were in the 21-60 year age-group [ 15 ]. Trauma predominantly occurs in the young adult male with road traffic accidents being the leading aetiological factor [ 4 , 5 ]. The young adults are very energetic and mobile.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma predominantly occurs in the young adult males with road traffic accident being the leading aetiological factor [ 4 , 5 ]. Most deaths following trauma are associated with multiple injuries (60.9%) and head injuries (30.4%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%